Formation and Capasity Building Of Herbal Healthy Cadre in Api-Api Village, Wonokerto, Pekalongan Regarding TOGA - Wirasti Wirasti; St. Rahmatullah; ulian Wahyu Permadi (Prosiding University Research Colloquium, 2022)
VillageApi-apui WonokertoDisctrict,PekalonganRegency locatedapproximately6 km to the north Pantai Utara Jawa (Pantura). The livelihoods of the Api-api villages communityisfisherman,pond farmers,convectionfarmers, rice farmer ect. The health level of the Api-Api community was initially relatively good because awareness for treatment was good, but after the rob and the covid-19 pandemic, the health of the community village declined and the environment became less well -maintained. To support and further improve the level of public health, it necessary to form herbal healthy cadre. The aim of this activity servicecommunityis to increase and empower community in Api-Api Vilage, Wonokerto District, Pekalongan Regency. The Service vommunityiscarriedout inseveralstage. The first stage:observation,thesecondstage is a shared perceptionwith thevillagehead,the thirdstageiscounselingon how to plant family medicinalplants(TOGA),the fourth stage istrainingon how to select and growmedicinal plants. ThisMethodsactivity iscollaborationwith the villagegovermantand training. The results of this activity is an increase inknowledgeandundrstandingof herba; healthy cadres in Api-Api Village by 38,2%. The community (Herbal healthy cadres) incerased their knowledge about how select and grow medicinal plant . TheConclusionthis activityis to increase capacityofknowledgeplantmedicinaland how toselectas well as plantTOGA.